2008
DOI: 10.1111/j.1538-4616.2008.00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbolic Discounting and the Phillips Curve

Abstract: Using a standard dynamic general equilibrium model, we show that the interaction of staggered nominal contracts with hyperbolic discounting leads to in ‡ation having signi…cant long-run e¤ects on real variables.JEL Classi…cation: E20, E40, E50

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 72 publications
(68 reference statements)
1
37
0
Order By: Relevance
“…Graham and Snower (2008) show that the presence of nominal wage contracts breaks this observational equivalence in the sense that an econometrician estimating both the Euler equation and the long-run Phillips curve could distinguish an economy with hyperbolic discounting from one with exponential discounting.…”
Section: Introductionmentioning
confidence: 99%
“…Graham and Snower (2008) show that the presence of nominal wage contracts breaks this observational equivalence in the sense that an econometrician estimating both the Euler equation and the long-run Phillips curve could distinguish an economy with hyperbolic discounting from one with exponential discounting.…”
Section: Introductionmentioning
confidence: 99%
“…Graham and Snower (2004) was extended in a number of di¤erent directions. Graham and Snower (2008) showed that under hyperbolic time discounting positive money non-superneutralities are more sizeable than under exponential discounting. Vaona andSnower (2007, 2008) showed how the shape of the long-run Phillips curve depends on the shape of the production function.…”
Section: Introductionmentioning
confidence: 99%
“…On these grounds, vector autoregressions (VARs), 19 with their exclusive focus on the IRFs of the system offered a statistically robust (albeit economically sterile) alternative. VARs were heavily criticized 17 Note that the simultaneous equation literature refers to "direct" and "indirect" effects of the exogenous variables instead of "local" and "global" effects. The reason we choose the latter terminology is that indirect=global-direct, where direct=local.…”
Section: Evaluating Macro Models: "Global" Versus "Local" Elasticitiesmentioning
confidence: 99%
“…We refer to the individual equation elasticity as the "local" one and we distinguish it from the "global" elasticity which takes into account all the relevant spillover effects in the multi-equation system. 17 The global elasticities are obtained by the impulse response function (IRF) of an endogenous variable with respect to a one-off unit change (shock) in an exogenous variable. In stable dynamic models, the effects of a shock persist after the shock is over and gradually dissipate with the passage of time.…”
Section: Evaluating Macro Models: "Global" Versus "Local" Elasticitiesmentioning
confidence: 99%